Fascioliasis and intestinal parasitoses affecting schoolchildren in Atlixco, Puebla State, Mexico: epidemiology and treatment with nitazoxanide. - José Lino Zumaquero-Ríos; Jorge Sarracent-Pérez; Raúl Rojas-García; Lázara Rojas-Rivero; Yaneth Martínez-Tovilla; María Adela Valero; Santiago Mas-Coma (Public Library of Science (PLoS), 2013)
Background The Atlixco municipality, Puebla State, at a mean altitude of 1840 m, was selected for a study of Fasciola hepatica infection in schoolchildren in Mexico. This area presents permanent water collections continuously receiving thaw water from Popocatepetl volcano (5426 m altitude) through the community supply channels, conforming an epidemiological scenario similar to those known in hyperendemic areas of Andean countries. Methodology and findings A total of 865 6-14 year-old schoolchildren were analyzed with FasciDIG coproantigen test and Lumbreras rapid sedimentation technique, and quantitatively assessed with Kato-Katz. Fascioliasis prevalences ranged 2.94-13.33% according to localities (mean 5.78%). Intensities were however low (24-384 epg). The association between fascioliasis and the habit of eating raw vegetables was identified, including watercress and radish with pronouncedly higher relative risk than lettuce, corncob, spinach, alfalfa juice, and broccoli. Many F. hepatica-infected children were coinfected by other parasites. Entamoeba histolytica/dispar, Giardia intestinalis, Blastocystis hominis, Hymenolepis nana and Ascaris lumbricoides infection resulted in risk factors for F. hepatica infection. Nitazoxanide efficacy against fascioliasis was 94.0% and 100% after first and second treatment courses, respectively. The few children, for whom a second treatment course was needed, were concomitantly infected by moderate ascariasis burdens. Its efficacy was also very high in the treatment of E. histolytica/E. dispar, G. intestinalis, B. hominis, H. nana, A. lumbricoides, Trichuris trichiura, and Enterobius vermicularis. A second treatment course was needed for all children affected by ancylostomatids. Conclusions Fascioliasis prevalences indicate this area to be mesoendemic, with isolated hyperendemic foci. This is the first time that a human fascioliasis endemic area is described in North America. Nitazoxanide appears as an appropriate alternative to triclabendazole, the present drug of choice for chronic fascioliasis. Its wide spectrum efficacy against intestinal protozooses and helminthiasis, usually coinfecting liver fluke infected subjects in human endemic areas, represents an important added value.